O ENSINO DE FILOSOFIA E O NOVO ENSINO MÉDIO: DIALOGANDO COM DOCENTES SOB A ESCUTA DA TRADIÇÃO - SOUSA, Beatriz Lorena de (2023)
The current movements in educational curricular policies started from a panorama that did not consider the basic education teacher as a source of knowledge about the Brazilian educational reality, which led this research to give voice and listen to this educators to understand this change in the environment educational, starting from those that are founding pieces for teaching. This research also tried to understand the mobilizations and resistance manifested in relation to the National Common Curricular Base (BNCC). In this way, this research investigated how the Philosophy teachers of Basic Education in São Luís, Maranhão, are experiencing the structuring and follow the implementation of the BNCC in the process of school education, with the objective of knowing the directions and the effects that this document has caused to the work of the philosophy teacher, in order to understand the impacts of these changes in the teaching of this curricular component in the context of São Luis. The perspective of this analysis considered the educators' understanding of the changes through methodological guidelines raised by the process of hermeneutic phenomenology proposed by Hans-Georg Gadamer (1900-2002) in the works Verdade and Method I and II (1997 and 2002, respectively) and critical education with the thinker Paulo Freire (1921-1997), in the book Pedagogia da Autonomia (1996). This hermeneutic approach was used in the course of the research and, mainly, to better understand the last part of the investigation that brought semi-structured interviews carried out on Google meet, with professors of philosophy who had already taught in this field in the intervals of 1980 up to the present time, followed by a questionnaire of multiple-choice questions created by Google forms with teacherse who currently teach Philosophy in São Luís. This part of the analysis was intended to perceive these subjects of education through the authors Gadamer and Freire collaborating with their ideas about dialogue and education. The results of this research show that the curriculum policies brought by the BNCC, in the way it was structured and imposed in the school context, ended up leading philosophy teachers to a position of confrontation and social mobilization, through contestation, clashes, conflicts and actions to guarantee the maintenance of philosophy teaching.